Assessing and giving feedback to students' written work : an expert-novice study using verbal protocol analysis / Clarence Jerry - Jerry, Clarence (2012)
The study aimed to examine and gain insight on how the practice of the expert raters in assessing and giving feedback on students’ writing can be translated into a mental model that can be used in training to help the novice raters acquire the skill of an expert rater in assessing ESL students’ writing effectively. The study was carried out in two phases. In phase one, the study contributes to the body of knowledge by uncovering the cognitive difference between the expert and novice raters while assessing and giving feedback on students’ writing. The transcripts of verbal protocol Analysis (VPA) and interviews were analysed, using a coding scheme, to identify the knowledge states and conceptual operators used by the expert and novice raters, which were also their personal justification on the decision and action taken while doing the process of “thinking aloud”. The findings in phase one of the study helped the researcher in understanding how an expert rater could be differentiated from the novice rater in terms of their mental cognitive processes. The lines of reasoning embedded in the expert raters’ responses to students’ writing were drawn from this analysis and translated into a conceptual mental model. Apart from getting a better understanding of the constructs in the mental model, phase two of the study also focused on the feasibility of using this mental model in a training/workshop to reduce the differences between the expert raters and novice raters in terms of skills in assessing and evaluating writing. Five participants out of twenty five novice raters who came for the workshop were interviewed in a preliminary probe into the usefulness of the mental model in training to help novice rater acquire the skills of an expert rater in assessing writing.